Clinical practice guidelines for the care of psychologically distressed bereaved families who have lost members to physical illness including cancer. (6th March 2022) - Akechi, Tatsuo; Kubota, Yosuke; Ohtake, Yoichi; Setou, Noriko; Fujimori, Maiko; Takeuchi, Emi; Kurata, Akiko; Okamura, Masako; Hasuo, Hideaki; Sakamoto, Ryo; Miyamoto, Seraki; Asai, Mariko; et al.
Abstract: The Japanese Psycho-Oncology Society and the Japanese Association of Supportive Care in Cancer developed evidence-based clinical practice guidelines for the care of psychologically distressed bereaved families who have lost members to physical illness including cancer. The guideline development group formulated two clinical questions. A systematic literature review was conducted. The level of evidence and the strength of the recommendations were graded and recommendation statements validated using the modified Delphi method. The recommendations were as follows: non-pharmacological interventions were indicated for serious psychological distress (depression and grief); antidepressants were indicated for depression; however, psychotropic medications including antidepressants were not recommended for 'complicated' grief. These guidelines will facilitate the provision of appropriate care to distressed bereaved family members and highlight areas where further research is needed. Abstract : The first clinical practice guidelines to optimize care for psychologically distressed bereaved families who have lost a member to physical illness were devised using the formal guideline development method.